Linkage Between foreign Direct Investment, Trade and Trade Policy An Economic Analysis with Application to the Food Sector in OECD Countries and Case Studies in Ghana, Mozambique, Tunisia and Uganda - Wilson, Norbert (OECD Publishing, 2007)
Through empirical analysis and case studies, this document explores the relationships amongst foreign direct investment (FDI), trade and trade-related policies in OECD and four African countries (Ghana, Mozambique, Tunisia and Uganda). In OECD countries, tariffs and market price support may have an effect on how FDI is distributed geographically. FDI may be used to avoid or "jump" tariffs. Also, investors in a home country may invest in a host country to exploit the preferential tariffs that the host has with a third country. Participation in a regional trading agreement or customs union, e.g. NAFTA or the EU, may create investment opportunities. Market price support to agriculture may encourage outward investment and discourage inward investment. In aggregate, FDI and trade appear to complement one another. The four case studies in Africa highlight the interactions amongst regulations, foreign investment and trade. For example, FDI is useful in helping the firm develop the resources to meet the standards of OECD markets. Investment promotion agencies and export processing zones appear to prepare countries to attract FDI. Preferential trading agreements like the Everything but Arms with EU and the African Growth Opportunity Act with the US may have an impact on trade and investment. Beyond trade policies, other policies and factors contribute substantially to the location and distribution of FDI. As seen amongst OECD countries, factors like the GDP of a country (i.e. market size) and cost of production and transport can have an effect on FDI. Another factor that influences FDI is the degree of market competitiveness. For the four African countries, the country risk and the level of infrastructure can influence the volume of FDI attracted
Keywords: Trade; Ghana; Mozambique; Tunisia; Uganda